Modelled distributions and conservation priorities of wild sorghums (Sorghum Moench) - Myrans, Harry; Diaz, Maria V.; Khoury, Colin K.; Carver, Daniel; Henry, Robert J.; Gleadow, Roslyn (Wiley, 2020)
Aim: To fill knowledge gaps regarding the distributions, ecogeographic niches and conservation status of sorghum's wild relatives (Sorghum Moench). Location: The study covered the potential native ranges of wild Sorghum taxa worldwide, including Australia, New Guinea, Asia, Africa and Central America. Methods: We modelled the distributions of 23 wild Sorghum taxa, characterized their ecogeographic niches, assessed their conservation status both ex situ and in situ and performed preliminary threat assessments. Results: Three taxa were categorized as “high priority” for further conservation based on their ex situ and in situ assessments, with a further 19 as “medium priority” and only one as “low priority”. The preliminary threat assessment indicated that 12 taxa may be Endangered, four Vulnerable and four Near Threatened. The taxa fill a wide range of climatic niches, both across and within taxa, including temperatures and precipitation. Main conclusions: Taxon richness hotspots, especially in northern Australia, represent hotspots for conservation action, including further seed collection and habitat protection, with Sorghum macrospermum E. D. Garber being the highest priority for increased in situ protection. Outside Australia, Sorghum propinquum (Kunth) Hitchc. stands out for further ex situ conservation, especially given its close relationship to the crop